Methodological proposal with an interdisciplinary approach for teaching learning content theory of the pharmacological receptor in the medical career - Yeny Dueñas Pérez; Ana María Ramos Cedeño; Belkis Barrios Romero; Alicia del Rosario Ramírez Pérez; Yacelis Dahilet Cisneros Nápoles; Mirtha Amarilis Hernández López (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: in therapeutic decision-making, the importance of knowledge of the drug receptor theory content is recognized; however, there is a lack of proposals from interdisciplinarity, which is useful as reference for teachers to improve the teaching of this process. Objective: to design a methodological proposal with an interdisciplinary approach for the teaching-learning of the content theory of the pharmacological receptor in the Medicine career. Methods: study carried out at the Cienfuegos University of Medical Sciences, during the 2018-2019 school year. From a universe of 250 fourth-year medical students, 75 students were selected through a simple random probability sampling, to whom a survey was applied. 19 professionals were surveyed corresponding to all the teachers involved in the process for teaching the subjects Pharmacology I, Molecular Biology and Nervous, Endocrine and Reproductive Systems. Five key informants selected by intentional non-probability sampling were interviewed. In addition, a documentary analysis was carried out that included the study plans and programs of the Medicine career in Cuba to identify the interrelationship between the disciplines. Results: based on the weaknesses detected, a proposal was elaborated that will facilitate the linking of the subjects, which will allow greater importance and relevance of the knowledge and pharmacological skills in medical training from an interdisciplinary perspective. Conclusions: the experts considered that the proposal will contribute favorably to the preparation of teachers in response to the current medical training model.